Literasi dan Efikasi Keuangan Terhadap Keputusan Investasi Mahasiswa Tingkat Akhir Berbasis Penerapan Teknologi Informasi - Andy Hakim (Forum Kerjasama Pendidikan Tinggi, 2020)
Students are high-level students who are very mature and are able to deal with financial problems, there are many students who have thought ahead by thinking about financial problems and their future which will be directed to the future, having good thinking is a reflection of the success of Education to change a brighter future. This study looks at the effect of financial literacy and financial efficacy of final-year students who later have an interest in investing, the results of the study show that the level of student financial literacy is very good which shows the ability in financial processing in a stable state and the financial efficacy of students, that is of positive value so that affect the level of investment interest decisions